Potential risk factors of pediatric acute respiratory distress syndrome in sepsis - Saragih, Kezia Theofani; Malisie, Ririe Fachrina; Daulay, Rini Savitri; Sitepu, Bobby Ramses Erguna (Indonesian Pediatric Society, 2024)
Background Sepsis in children is characterized by a dysregulated host response to infection and life-threatening organ dysfunction. Pediatric acute respiratory distress syndrome (PARDS) is a severe complication of sepsis. Several known risk factors of PARDS are immunodeficiency, obesity, source of infection, and genetic factors. Objective To describe the potential risk factors of PARDS in septic children at Haji Adam Malik General Hospital, Medan, North Sumatera. Methods This descriptive study using eligible medical record data from sepsis patients aged 1 month – 18 years was conducted at Haji Adam Malik General Hospital in 2020–2022. A total sampling method was used for subject selection. Patients’ demographic and clinical characteristics, mechanical ventilation modes and parameters, laboratory results, and outcomes were collected from medical records. Patients were classified as having sepsis with PARDS if Pediatric Acute Lung Injury Consensus Conference (PALICC) criteria of ARDS was met. Results Of 112 pediatric sepsis patients, 33.9% developed PARDS. The mortality rates for PARDS was 73.7%. Of the patients with PARDS, 57.9% had immunodeficiency, 60.5% patients had an intrapulmonary infection, 39.5% had an extrapulmonary infection, and 23.7% of patients had a suspected genetic disorder. In addition, 39.5% had good nutritional status, followed by 21.1% with obese. Conclusion The majority of patients with PARDS have intrapulmonary infection and immunodeficiency. Some of patients with PARDS have suspected genetic disorders and well nourished.